Metabolic syndrome-associated osteoarthritis. Issue 2 (March 2017) - Courties, Alice; Sellam, Jérémie; Berenbaum, Francis
Abstract : Purpose of review: Interest in the metabolic syndrome-associated osteoarthritis phenotype is increasing. Here, we summarize recently published significant findings. Recent findings: Meta-analyses confirmed an association between type 2 diabetes and osteoarthritis and between cardiovascular diseases and osteoarthritis. Recent advances in the study of metabolic syndrome-associated osteoarthritis have focused on a better understanding of the role of metabolic diseases in inducing or aggravating joint damage. In-vivo models of obesity, diabetes, or dyslipidemia have helped to better decipher this association. They give emerging evidence that, beyond the role of common pathogenic mechanisms for metabolic diseases and osteoarthritis (i.e., low-grade inflammation and oxidative stress), metabolic diseases have a direct systemic effect on joints. In addition to the impact of weight, obesity-associated inflammation is associated with osteoarthritis severity and may modulate osteoarthritis progression in mouse models. As well, osteoarthritis synovium from type 2 diabetic patients shows insulin-resistant features, which may participate in joint catabolism. Finally, exciting data are emerging on the association of gut microbiota and circadian rhythm and metabolic syndrome-associated osteoarthritis. Summary: The systemic role of metabolic syndrome in osteoarthritis pathophysiology is now better understood, but new avenues of research are being pursued to better decipher the metabolic syndrome-associated osteoarthritis phenotype.